Phylogeography of the widespread creek chub Semotilus atromaculatus (Cypriniformes: Leuciscidae). Issue 5 (29th November 2018) - Schönhuth, Susana; Gagne, Roderick B.; Alda, Fernando; Neely, David A.; Mayden, Richard L.; Blum, Michael J.
Abstract : The extent and nature of genetic differentiation in Semotilus atromaculatus, one of the most abundant and widespread leuciscids in North America, were evaluated based on mitochondrial (mt) and nuclear DNA sequence variation. Phylogenetic relationships were first inferred based on a fragment of the cytochrome b ( cytb ) region and the nuclear intron s7 gene for S. atromaculatus and all other congeners as well as representative species from all other genera in the creek chub–plagopterin clade. The phylogeography of major haplogroups of S. atromaculatus was also assessed according to variation in a fragment of the mitochondrial cytb region from 567 individuals across its range. All analyses identified S. thoreauianus, S. lumbee and S. corporalis as reciprocally monophyletic groups. Analyses of nuclear sequence variation resolved S. atromaculatus as a single clade, where S. thoreauianus and S. lumbee were recovered as the sister group to S. atromaculatus, and S. corporalis was resolved as sister to all other species in the genus. Analyses of mtDNA sequence variation recovered S. atromaculatus as three well supported and differentiated monophyletic groups, with a widespread genetically homogeneous lineage extending across most of the current range of the species; a more geographically restricted and geographically structured lineage in the southern Appalachians, sister group to S. lumbee ; and a geographically restricted lineage was identified from two Gulf Slope basins. Evidence of complex mito‐nuclear discordance and phylogeographic differentiation within S. atromaculatus illustrates that further analysis of widespread species is warranted to understand North American freshwater fish diversity and distributions.